Idiopathic normal pressure hydrocephalus with synucleinopathy: Diagnosis and treatment. (31st December 2021) - Han, Sang‐Won; Park, Young Ho; Ryoo, Nayoung; Kim, Kitae; Pyun, Jung Min; Kim, Sangyun
Abstract: Background: Idiopathic normal pressure hydrocephalus (iNPH) is characterized by the classic triad of gait disturbance, urinary incontinence, and cognitive impairment in the presence of ventriculomegaly, which is ameliorated by the removal of CSF, and is diagnosed by excluding known risk factors for communicating hydrocephalus including meningitis, traumatic brain injury, subarachnoid hemorrhage, and brain irradiation. Shunt surgery is indicated for iNPH patients who respond to the removal of CSF. Method: A 70‐year‐old man presented with a 2‐year history of progressive disturbances of gait, balance, control of urination, and cognition. His family reported that he exhibited dream enactment behavior. Brain MRI showed enlarged lateral ventricles and disproportionately enlarged subarachnoid space hydrocephalus. Although our iNPH patient whose gait disturbance was improved by lumbar puncture with CSF removal, FP‐CIT PET showed reduced DAT binding bilaterally throughout the striatum, including the caudate nucleus and the putamen. Result: It is known that patients with iNPH present with normal presynaptic DAT binding in the striatum. However, although our iNPH patient's gait disturbance was improved by LP with CSF removal, FP‐CIT PET showed reduced DAT binding throughout the striatum. Given that 25% of iNPH patients who underwent shunt surgery were revealed to have a diagnosis other than iNPH, we supposed our patient might have a concomitant neurodegenerative disorder affecting presynaptic nigrostriatal neurons. His dream enactment behavior suggests underlying synucleinopathy. Recently, Broggi et al. reported that the striatal dopaminergic deficit on DAT scan was common (46.7%) in patients with iNPH. And the long‐term outcome of shunt surgery of patients with abnormal DAT scan was not favorable. Furthermore, it is also known that the improvement of gait after the removal of CSF rarely persists for more than a few days in patients with iNPH. However, the response after CSF removal sometimes could be sustained, as in our patient, for a few months, which might be attributed to the elasticity of the ventricular wall. Conclusion: For iNPH patients with clinical features suggesting synucleinopathy such as REM sleep behavior disorder, DAT scan could be considered to identify concurrent synucleinopathy before shunt surgery, even in cases with initial response to high‐volume lumbar puncture.